Evaluation of impact of an integrated lecture method of teaching among undergraduate medical students, compared to traditional didactical lectures in reference to antenatal care - Behera, Basanta Kumar; Agasti, Narahari; Sahoo, Kamalakanta (International Journal of Advances in Medicine, 2017)
Background: In traditional lecture method of teaching most of the time there is time consumption, duplication and overlapping of topics taught in the MBBS course. Integration (both horizontal and vertical) of subjects improves the cognitive and psychomotor domains of students to enhance their skills to correlate clinically to obtain an accurate diagnosis. Methods: The present study comprised of 96 students of 3rd semester MBBS course. A pretested questionnaire was given to study their existing level of knowledge and attitude regarding antenatal care. The students were divided into two groups by simple random method - a study group of 48 students, who receive integrated teaching including didactic lectures, case studies and live demonstrations by department of Community Medicine and Obstetrics and Gynaecology, whereas the control group of 48 students received only didactic lectures. Post test was conducted after 3 days. The mean knowledge and attitude scores of pre-test and post-test of the two groups were analyzed by using Z- test. Results: In the post test, the mean knowledge score between traditional and integrated groups were 12.40 and 14.46 respectively with standard deviation of 1.869 and 1.864. Whereas the mean values of attitude is 36.95 and 60.00 with standard deviation of 1.972 and 1.977. There was a significant improvement in both knowledge and attitude of students of integrated group as compared to traditional group (P<0.001). Conclusions: Integrated method of teaching was found to be more effective than traditional lecturing method.